2020
DOI: 10.5194/acp-20-9547-2020
|View full text |Cite
|
Sign up to set email alerts
|

Towards the connection between snow microphysics and melting layer: insights from multifrequency and dual-polarization radar observations during BAECC

Abstract: Abstract. In stratiform rainfall, the melting layer (ML) is often visible in radar observations as an enhanced reflectivity band, the so-called bright band. Despite the ongoing debate on the exact microphysical processes taking place in the ML and on how they translate into radar measurements, both model simulations and observations indicate that the radar-measured ML properties are influenced by snow microphysical processes that take place above it. There is still, however, a lack of comprehensive observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…When thermodynamic information is available, radio-wave propagation models can be used to estimate radar signal attenuation by atmospheric gases. Here we use the MPM93 model, an updated version of the millimeter-wave propagation model described by Liebe (1985) and Liebe et al (1993) to compute two-way gas attenuation of X-, Ka-, Wand G-band signals for the conditions that occurred at 12:00 and 15:44 UTC on 25 February 2020 when two radiosondes were launched. Figure 2a and b show the profiles of temperature, dew-point temperature and humidity recorded at the US NWS site 22 km east of SBRO at 12:00 UTC and at the SBRO at 15:44 UTC.…”
Section: Gaseous Attenuation Correctionmentioning
confidence: 99%
“…When thermodynamic information is available, radio-wave propagation models can be used to estimate radar signal attenuation by atmospheric gases. Here we use the MPM93 model, an updated version of the millimeter-wave propagation model described by Liebe (1985) and Liebe et al (1993) to compute two-way gas attenuation of X-, Ka-, Wand G-band signals for the conditions that occurred at 12:00 and 15:44 UTC on 25 February 2020 when two radiosondes were launched. Figure 2a and b show the profiles of temperature, dew-point temperature and humidity recorded at the US NWS site 22 km east of SBRO at 12:00 UTC and at the SBRO at 15:44 UTC.…”
Section: Gaseous Attenuation Correctionmentioning
confidence: 99%
“…The measurements used in this study were collected at Station for Measuring Ecosystem -Atmosphere Relations II (Hari and Kulmala, 2005;Petäjä et al, 2016) (Küchler et al, 2017) (HYytiälä Doppler RAdar, HYDRA-W) has been operating at the station. The radar is pointing vertically and measures radar signal spectral moments, LDR and dual-polarization Doppler spectra; see Li and Moisseev (2020) for the example of the data. The LDR decoupling is about 30 dB, so the minimum observable LDR is about −30 dB.…”
Section: Cloud Radar Observationsmentioning
confidence: 99%
“…For vertically pointing Ka-and W-band radars, ice columns usually produce LDR values as high as −15 dB, which is distinctively higher than that of most other ice particle types (Aydin and Walsh, 1999;Tyynelä et al, 2011). Oue et al (2015), Li and Moisseev (2020), Luke et al (2021), andLi et al (2021) have shown that this strong LDR signal at the slow falling part of the radar Doppler spectrum can be used to identify columnar-ice crystals. In this study, this method is applied to long-term radar Doppler spectra observations for characterizing the production of columnar-ice particles in stratiform clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Using these retrieved masses m and the maximum dimensions of the observed particles, D max , we first estimated the rime fraction. The mass of unrimed snow, m us is assumed as in Moisseev et al (2017); Li et al (2020):…”
Section: Sampling Of Training Datamentioning
confidence: 99%
“…Mason et al (2018) developed an optimal estimation retrieval to obtain a density factor parameter, which is sensitive to riming, using observations of mean Doppler velocity (MDV) and DWR Ka,W . Li et al (2020) developed a snow observation classification with a rimed and an unrimed category, using MDV and DWR X,Ka . Oue et al (2021) combined MDV, DWR Ka,W with polarimetric observations and were able to observe even different stages of the riming process.…”
Section: Introductionmentioning
confidence: 99%